Upaya Peningkatan Kesadaran Masyarakat terhadap Stunting pada Balita serta Peningkatan Gizi melalui Pengembangan Potensi Desa - Rani Tiara Desty; Wahyuni Arumsari (Puslitbang Sinergis Asa Professional, 2022)
Stunting is a chronic malnutritional problem identified by a shorter than normal. Children who suffer from stunting are more susceptible to infectious diseases, and as adults are at risk for degenerative diseases.The prevalence of stunting in Klaten Regency has increased. In 2021 the prevalence of stunting in Klaten Regency is 8.9%, while in 2022 it is 9.3%. One of the government policies to overcome stunting is to increase the efficiency of the food and nutrition information system. Methods to increase public awareness regarding stunting and improvement of under-five nutrition include: observation of village potential, seminars and discussions. The target of community service activities is the PKK community in Polanharjo District, Klaten Regency. Based on the post test results, it was found that there was a significant increase in participants' knowledge, namely 41%, in understanding the risk factors that cause stunting. By knowing and understanding stunting information, the community can apply stunting prevention behavior properly, through the supervision of cadres and health workers in their area.